A two-layer multi-energy management system for microgrids with solar, wind, and geothermal renewable energy - Xu, Da; Zhong, Feili; Bai, Ziyi (Frontiers in Energy Research, 2023)
The inherent intermittency of high-penetrated renewable energy poses economic and reliable issues of microgrid energy management. This paper proposes a two-layer predictive energy management system (PEMS) for high-renewable multi-energy microgrid (MEM). In this MEM, geothermal-solar-wind re-newables is converted and conditioned for electricity, thermal, gas supplies, in which multi-energy complementarities are fully exploited based on electrolytic thermos-electrochemical effects. The pro-posed microgrid multi-energy management is a complicated and cumbersome problem due to their increasingly tight energy couplings and uncertainties of renewable energy sources (RESs). This intrac-table problem is thus processed by means of a two-layer PEMS with different time scales, where the system operating costs are minimized in the upper layer and the renewable fluctuations are coped with in the lower layer. Simulation studies on a high-renewable MEM are provided to indicate its ef-fectiveness and superiority over single time scale scheme. Simulations results show that the operating cost can be reduced by 22.2% with high RESs accommodation.